043 Rheumatoid leptomeningitis: an acute presentation of neuropsychiatric disturbance. Issue 6 (24th May 2018) - Lubomski, Michal; Sy, Joanne; Buckland, Michael; Lee, Andie S; Richards, Bethan; Thompson, Elizabeth; Fulham, Michael; Halmagyi, Michael
Abstract : Introduction: We report a case of an isolated acute neuropsychiatric presentation due to rheumatoid meningitis (RM), successfully treated with steroids and rituximab. Case: A 41 year old man with a chronic headache and acute neuropsychiatric disturbance including impulsivity, grandiose delusions and agitation on a background of no known psychiatric history. Incidentally, he reported migratory palindromic, large and small joint polyarthritis over the preceding 18 months accompanied by headache, symptomatically treated with indomethacin. He had no prior diagnosis of rheumatoid arthritis (RA) or other connective tissue disorder. Serum and cerebrospinal fluid (CSF) cyclic citrullinated peptide antibodies were strongly positive, with a normal serum rheumatoid factor. An interferon-gamma release assay was positive, suggestive of prior tuberculosis (TB) exposure. CSF examination was unremarkable with an MRI brain demonstrating asymmetric features of leptomeningeal thickening and enhancement over both cerebral cortices, suggesting an inflammatory or infiltrative leptomeningitis. Lymphoma, IgG4–related disease, granulomatous diseases such as TB, granulomatosis with polyangiitis, neurosarcoidosis, neurosyphilis and meningeal metastasis were considered as differential diagnoses. A leptomeningeal and brain biopsy showed necrotising inflammation with ill-defined granulomas and a dense lymphoplasmacytic infiltrate. No organisms were identified. Mycobacterial polymerase chain reaction and cultures over three months were negative. RM was the favoured histological diagnosis. Empirical treatment for prior TB exposure was commenced in conjunction with steroids. Subsequent addition of iv rituximab resulted in sustained improvement of neuropsychiatric and joint symptoms. Conclusion: This report illustrates for the first time isolated acute neuropsychiatric disturbances attributable to RM without a prior history of RA that was responsive to rituximab. Clinicians should consider infiltrative and inflammatory leptomeningeal causes, particularly with asymmetric meningeal thickening and enchantment on MRI and should commit to a tissue biopsy when no other systemic connective tissue, infective or neoplastic causes are identified.